STONE DUSH SEBAGAI PENGGANTI AGREGAT TERHADAP BETON NORMAL - Huda, Imam Al; Lingga, Andry Alim; Budi, Gatot Setya (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
Construction of the structure and infrastructure in Indonesia began to rapidly return. Civil buildings are usually constructed using a base material in the form of concrete and teel. Concrete used isusually a mixing between the coarse aggregate (gravel), fine aggregate (sand), cement, and water. The material used in the manufacture of concrete are materials culled from nature so that it can be called as natural resources. Makers of concrete material is largely natural resources that cannot be renewed. Natural resources that cannot be renewed will gradually run out, it needs to be searched then need to look for a successor. Grey is a by-product of the stone-breaking machine in the process of solving the stone to stone broke the aggregate replacement materialscould be made smooth. However grey had many disadvantages such as water absorption greater than natural sand. In the writing of this blending of gray stone with fine aggregate in this case in the form of grey concrete planning quality f'c 25 MPa. In this case is expected to come by a good proportion so that the blending is obtained strong press optimum Keywords: grey,concrete Aggregate, fine, normal quality f'c 25 MPa, robust press